1990
DOI: 10.1002/1098-108x(199003)9:2<191::aid-eat2260090208>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the oral pathologies occurring in bulimia nervosa

Abstract: This study investigated oral pathologies associated with bulimia nervosa and examined the relationship between these pathologies and the bulimic's binge eating, vomiting, and postvomiting oral hygiene. Results revealed a greater prevalence of enamel erosion, dental caries, dentin hypersensitivity, parotid dysfunction, and xerostomia in the bulimic group when compared with a nonbulimic control group. Enamel erosion was related to the duration of vomiting behavior. After 6 months the majority of bulimics exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 16 publications
1
46
1
Order By: Relevance
“…Dental erosion can alter the aesthetics of bulimic women (Figs 2 and 3), provoke dental hypersensitivity and pain, 2,8 and result in tooth loss. 1 The literature on the treatment of bulimic patients is restricted to case reports of restoration of the damaged surfaces with porcelain-laminated veneers, dentin-bonded crowns with minimal tooth preparation, composites, and complete-coverage restorations.…”
Section: Treatmentmentioning
confidence: 99%
“…Dental erosion can alter the aesthetics of bulimic women (Figs 2 and 3), provoke dental hypersensitivity and pain, 2,8 and result in tooth loss. 1 The literature on the treatment of bulimic patients is restricted to case reports of restoration of the damaged surfaces with porcelain-laminated veneers, dentin-bonded crowns with minimal tooth preparation, composites, and complete-coverage restorations.…”
Section: Treatmentmentioning
confidence: 99%
“…Plaque levels and gingival condition were similar in eating disorder groups and controls (Milosevic and Slade, 1989), gingivae were reportedly healthier in anorexics and bulimics compared to controls (Philipp et al, 1991) and plaque levels were signi®cantly lower in the eating disorder groups (Touyz et al, 1993). Finally, Altshuler et al (1990) found no signi®cant differences in Gingival Index, Periodontal Index or Plaque Index between a bulimic and control group.…”
Section: Periodontal Diseasementioning
confidence: 76%
“…This seems logical given that eatingdisordered subjects demonstrated high positive personal perfectionism (Terry-Short et al, 1995) and might therefore be obsessive with respect to oral hygiene which would also be re¯ected in plaque levels and gingival health. Unfortunately, the results regarding caries remain equivocal, since Altshuler et al (1990) reported no difference in Decayed Missing Filled Surfaces (DMFS) index between a bulimic group and a control group, yet con¯icted this by stating that the bulimics had a greater mean number of carious lesions. The relationship between caries and diet in these groups is less clear.…”
Section: Cariesmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21] Intraoral manifestations differ depending on the specific behaviors associated with the different types of eating disorders. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Intraoral manifestations differ depending on the specific behaviors associated with the different types of eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Physical manifestations associated with anorexia include lanugo (growth of fine body hair), loss of head hair as a result of malnutrition and loss of body fat, and weight changes ranging from being at a normal weight to being extremely thin in severe cases. 12,13,25,26 The dental hygienists_ role also extends to tertiary prevention (management of relapse) by way of regular oral checkups every 6 months. 22,23 Secondary prevention consists of early identification, referral, and treatment of those who exhibit signs and symptoms of eating disorders.…”
Section: Introductionmentioning
confidence: 99%